Pengaruh Belanja Daerah dan Tingkat Pengangguran Terbuka Terhadap Indeks Pembangunan Manusia Di Kabupaten/Kota Se-Provinsi Lampung - Hayrun Nisa Eka Afriliani; Marselina; Moneyzar Usman; Dedy Yuliawan; Heru Wahyudi (CV. Multi Kreasi Media, 2023)
This study aims to analyze the effect of the education sector in spending areas, the health sector in shopping areas and the level of open reaction to the human development index in district/city throughout Lampung Province. The methods and analytical tools used in this study are panel data regression. The dependent variable used is the human development index and the independent variables include the education sector spending area, the health sector spending area and the number of poor people. The best model obtained is the Fixed Effect Model. The results of the study show that spending areas for the education sector, spending areas for the health sector and open unemployment rates have a positive and significant effect on the human development index in district/city throughout Lampung Province.